Poly(imidazoled glycidyl methacrylate-co-diethyleneglycol methyl ether methacrylate) – A new copolymer with tunable LCST and UCST behavior in water. (21st November 2018) - Zhang, Ganwei; Lei, Jianbin; Wu, Longbo; Guo, Chenchen; Fang, Jialong; Bai, Renbi; Wyman, Ian
Abstract: A series of poly (imidazoled glycidyl methacrylate- co -diethylene glycol methyl ether methacrylate) copolymers (denoted as P (iGMA- co -MEO2 MA)) with different monomer compositions were synthesized and characterized. These copolymers exhibit lower critical solution temperature (LCST) behaviors as the mole ratio of iGMA to MEO2 MA in the copolymers range from 0/100 to 1/1, and upper critical solution temperature (UCST) behaviors when this mole ratio ranges from 4/1 to 10/1. The thermoresponsive behaviors of these copolymers were also investigated in water at different pH values. The LCST of the copolymer increased with the iGMA content in the copolymer at pH 6.5, and changed little at pH 7.0, while it decreased with the iGMA content in the copolymer at pH 7.5. Meanwhile, the UCST of the copolymer increased with the iGMA content in the copolymer at pH 6.5 and 7.0. In addition, the thermoresponsive properties of P (iGMA- co -MEO2 MA) were influenced by the presence of salt and by the copolymer concentration. This paper offers a facile approach toward thermoresponsive materials with tunable LCST and UCST behaviors. Graphical abstract: Highlights: A novel family of P (iGMA- co -MEO2 MA)) copolymers were synthesized and characterized. The copolymers exhibit either LCST or UCST behaviors in water at different monomer compositions. The thermoresponsive behaviors of these copolymers were also investigated at different pH values. The thermoresponsive properties of P (iGMA- co -MEO2 MA) were influenced by salt addition and by the copolymer concentrations.